ANALISIS MINAT MAHASISWA TERHADAP KEWIRAUSAHAAN DENGAN KEINGINAN KERJA MAHASISWA SETELAH LULUS PADA MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS PEKALONGAN - Dwi Susilo; Kartono Muhammad (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
The purposes of the research are : How many student university of management study program  who  are  interested  in  enterprenuership,  The  need  of  work  after  their graduation  and  how  many  student  who  are  needs  in  enterprenuership.  The  interest effect  of  student  university  towards    the  need  of  their  work,  with  the  90  sample  of student  the  results  of  the  research  are  :  47  or  52%    sample  of  student  university interest  in  public  servant  or  private  official,  54  or  60%  sample  of  student  university the  want  to  be    of  enterprenuer    after  their  graduation.  Asymp.  Sig  (2-sided)  in Pearson Chi-Square that is 0,730 more than 0,05, So, there is not correlation and not effect  between  the  interest  and  their  need  of  working  sample  of  student  university after graduation.  The Keywords : Interest, Need and Enterprenuership.